Macronutrient composition and Body Mass Index vary by season in college students - Haghighatdoost, Fahimeh; Malekahmadi, Mahsa; Onvani, Shokouh; Ramezani-Jolfaie, Nahid; Azadbakht, Leila (Progress in Nutrition, 2018)
Objective: To describe seasonal variation in food intake, body weight, body mass index (BMI) and mid- upper arm circumference (MUAC) in college students. Methods: In this follow-up study, 120 male and 180 female college students aged 18-35 years were enrolled. All participants were visited every 3 month (four sampling points: baseline and three consecutive quarters) for 1-year period. Dietary intakes were assessed using seven- to nine-day food records on randomly selected days per quarter. Anthropometric measurements were performed by a trained dietetic according to standard protocol at four time points (12 to 15 weeks apart). Results: Daily caloric and carbohydrate intakes were higher by 193 kcal and 8% of total daily calorie intake during the summer compared to the winter. Fat intake was consumed in greater amount in the winter rather than other seasons. The highest weight and BMI were observed in the summer (72.9±4.6 kg and 26.22±5.3 kg/m2, respectively), whereas the lowest values were in the winter (68.7±3.6 kg and 24.7±3.8 kg/m2, respectively). The greatest difference for MUAC was found between fall and winter (-2.80±0.25 cm; P=0.001). Conclusions: There are seasonal variations in diet and anthropometric measurements among college students. Therefore, it must be taken into account when counseling individuals about healthy habits as well as when designing nutritional epidemiology studies.